A Novel DNA Replication-Related Signature Predicting Recurrence After R0 Resection of Pancreatic Ductal Adenocarcinoma: Prognostic Value and Clinical Implications - Feng, Zengyu; Li, Kexian; Lou, Jianyao; Ma, Mindi; Wu, Yulian; Peng, Chenghong (Frontiers in Cell and Developmental Biology, 2021)
The aim of any surgical resection for pancreatic ductal adenocarcinoma (PDAC) patients is to achieve tumour-free margin (R0). R0 margin is indicative of better outcome compared with positive margin (R1). But postoperative morbidity after R0 resection is still high and prognostic gene signature predicting recurrence risk of patients in this subgroup is blank. Our study aims to develop a DNA replication-related gene signature to stratify the R0 treated PDAC patients with different recurrence risk. We conducted Cox regression analysis and LASSO algorithm on 273 DNA replication-related genes and eventually constructed a 7-gene signature. The predictive capability and clinical feasibility of this risk model were assessed in both training set and external validation set. Pathway enrichment analysis showed that the signature was closely related to cell cycle, DNA replication and DNA repair, three key pathways involved in chemotherapy and radiotherapy response. These findings may shed light on the identification of novel biomarkers and therapeutic targets for PDAC.